1999
DOI: 10.1007/s004320050279
|View full text |Cite
|
Sign up to set email alerts
|

p53 mutations and codon 213 polymorphism of p53 in lung cancers of former uranium miners

Abstract: The results indicate that G-->T transversions do not seem to be very common mutations in p53 in lung cancers probably caused by radiation. Therefore, p53 may be mutated early in lung cancer development if radiation exposure is a critical factor in carcinogenesis. In accordance with studies of thyroid cancer patients in the Chernobyl region, our results may indicate an overrepresentation of codon 213/3 polymorphism in p53 in radiation-caused cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Popp et al [68] studied the lung cancers of 16 uranium miners (12 squamous cell carcinomas, 3 adenocarcinomas and 1 small-cell carcinoma) in Germany and 13 non-mining patients who had lung cancer (4 squamous cell carcinomas, 8 adenocarcinomas and 1 large cell carcinoma) and were all from the same geographical region. In line with many of the previous studies, they found no codon 249 G to T transversion in any of investigated patients, with the exception of the only non-smoking uranium miner present in the study.…”
Section: Genetic Effectsmentioning
confidence: 99%
“…Popp et al [68] studied the lung cancers of 16 uranium miners (12 squamous cell carcinomas, 3 adenocarcinomas and 1 small-cell carcinoma) in Germany and 13 non-mining patients who had lung cancer (4 squamous cell carcinomas, 8 adenocarcinomas and 1 large cell carcinoma) and were all from the same geographical region. In line with many of the previous studies, they found no codon 249 G to T transversion in any of investigated patients, with the exception of the only non-smoking uranium miner present in the study.…”
Section: Genetic Effectsmentioning
confidence: 99%
“…Deletions of 17p and TP53 mutations are frequent in human NSCLC, and have also been described in radon‐related tumors (Vahakangas et al, 1992; Taylor et al, 1994; Hollstein et al, 1997; Popp et al, 1999; Yngveson et al, 1999). No alteration within RNO 10, where the rat TP53 homolog is located, however, was observed in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have focused on TP53 and RAS gene mutations, mainly due to the frequent alterations of these genes in human lung carcinomas. One study described a specific codon 249 TP53 mutation in 31% of lung tumors from a cohort of uranium miners (Taylor et al, 1994), whereas others found a lower frequency without any specific hot‐spot mutations (Vahakangas et al, 1992; Hollstein et al, 1997; Popp et al, 1999; Yngveson et al, 1999). Similarly, the frequency of RAS mutations in radon‐related lung cancer has been rather low (Vahakangas et al, 1992; Johnson and Kelley, 1993) except for one study in which 9 of 23 lung adenocarcinomas contained mutation in the KRAS gene (McDonald et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The study of Popp et al indicated an overrepresentation of codon 213/3 polymorphism in p53 in radiation-caused cancers [69]. Some studies reported a radon-related TP53 hotspot in codon 249, exon 7.…”
Section: Genetics and Epigenetic Effects Of Radonmentioning
confidence: 99%